Worst of the Worst : Dealing with Repressive and Rogue Nations - Rotberg, Robert I. (Book collections on Project MUSE., 2007)
"Identifies and characterizes the most repressive states and singles out which are aggressive. Defines the actions constituting repression and proposes a method of measuring human rights violations, presenting an index of nation-state repressiveness. Offers a way to decide which repressive and rogue states are most deserving of strong policy attention"--Provided by publisher